Risks and challenges associated with NEOM project in Saudi Arabia: A marketing perspective - Areej Algumzi (Journal of Risk and Financial Management, 2022)
Saudi Arabia has proposed a new project, NEOM city, planned on the coast of the Red Sea with various unique and challenging features as a part of its vision 2030 to transform itself from an oil-dependent economy to knowledge-based economy. However, there are various risks and challenges associated with the project, the study of which is essential to effectively design and implement marketing and promotional strategies. Considering the large scale and scope of the project, the purpose of this study is to identify and evaluate the major contexts and associated risks in accordance with the planned city's objectives. An online questionnaire-based survey was used to collecting data related to the severity of the risks identified and classified in a literature review. A purposive sampling approach was adopted to select experts from various governmental institutions to participate in the study. A final sample of 417 expert participants was achieved from various ministries and departments in Saudi Arabia. Eleven risk factors and challenges were identified, including design challenges, as well as legal, contractual, operational, force majeure, human resources, financial, technological, political, environmental, and sociocultural risks. Risks related to human resources (mean impact = 4) and technology factors (mean impact = 4), as well as contractual risks (mean impact = 3.9), were identified to be very high, whereas environmental (mean impact = 2.7), legal (mean impact = 2.5), and force majeure (mean impact = 2.2) risks were identified to be of low severity. Managing mega projects requires effective planning and implementation, along with risk identification and mitigation mechanisms. In addition, it is essential to manage various influencing factors (especially government decisions) in the process of implementation to achieve success.
Keywords: 650; marketing; NEOM; mega projects; risk assessment; risk identification; risk severity